Spike count and morphology in the classification of epileptiform discharges - Aanestad, Eivind; Gilhus, Nils Erik; Olberg, Henning Kristian; Kural, Mustafa Aykut; Beniczky, Sándor; Brogger, Jan (Frontiers in Neurology, 2023)
Purpose The purpose of this study is to investigate the impact of Bergen Epileptiform Morphology Score (BEMS) and interictal epileptiform discharge (IED) candidate count in EEG classification. Methods We included 400 consecutive patients from a clinical SCORE EEG database during 2013–2017 who had focal sharp discharges in their EEG, but no previous diagnosis of epilepsy. Three blinded EEG readers marked all IED candidates. BEMS and IED candidate counts were combined to classify EEGs as epileptiform or non-epileptiform. Diagnostic performance was assessed and then validated in an external dataset. Results Interictal epileptiform discharge (IED) candidate count and BEMS were moderately correlated. The optimal criteria to classify an EEG as epileptiform were either one spike at BEMS > = 58, two at > = 47, or seven at > = 36. These criteria had almost perfect inter-rater reliability (Gwet’s AC1 0.96), reasonable sensitivity of 56–64%, and high specificity of 98–99%. The sensitivity was 27–37%, and the specificity was 93–97% for a follow-up diagnosis of epilepsy. In the external dataset, the sensitivity for an epileptiform EEG was 60–70%, and the specificity was 90–93%. Conclusion Quantified EEG spike morphology (BEMS) and IED candidate count can be combined to classify an EEG as epileptiform with high reliability but with lower sensitivity than regular visual EEG review.